Deformation mechanisms and work-hardening behavior of transformation-induced plasticity high entropy alloys by in -situ neutron diffraction. Issue 11 (2nd November 2018) - Fu, S.; Bei, H.; Chen, Y.; Liu, T.K.; Yu, D.; An, K.
ABSTRACT: A full picture of tensile deformation mechanism evolution in the FCC-to-HCP transformation-induced plasticity high entropy alloy (TRIP-HEA) was revealed by real-time in situ neutron diffraction. Three transition points, i.e. the triggering of TRIP in the FCC phase and the activation of single and multiple twinning in the HCP phase, were identified to result in significant stress redistribution. Accordingly, four deformation stages with distinct phase-specific work-hardening behaviors were recognized. It was concluded that the easily-triggered persisting TRIP and the work-hardening potential of the HCP contribute together to the persisting bulk work-hardening. GRAPHICAL ABSTRACT: IMPACT STATEMENT: The deformation mechanism evolution and phase-specific work-hardening behaviors of the FCC-to-HCP TRIP-HEA were unraveled, which provided a comprehensive understanding of the TRIP-assisted superior strength and ductility.